Division 2/zone 2 auxiliary devices - understanding global hazardous area requirements - Griffith, T.; D'Alleva, G.; Lockley, B.; Wood, B. (Record of Conference Papers Industry Applications Society 52nd Annual Petroleum and Chemical Industry Conference, 2005)
Under the auspices of the standards subcommittee within the Petroleum and Chemical Industry Committee (PCIC), IEEE recommended practice 303 auxiliary devices for rotating electrical machines in Class I, Division 2 and Zone 2 Locations has been radically updated to address worldwide requirements. Originally US based, this document is now expanded to include the Canadian Electrical Code, International Electrotechnical Commission (IEC), European Committee for Electrotechnical Standardization (CENELEC) and Standards Australia/New Zealand (AN/NZS) regulations. This paper highlights those improvements and serves as a short tutorial into current international codes for the implementation of "sometimes" hazardous electrical components, and is focused for North American engineers working on non-US projects. Included is a general subject overview and in particular, a discussion of similarities and differences between the codes.